The Mercosur-European Union agreements seen from the perspective of Argentina’s foreign policy - Alejandro Cesar Simonoff (Íconos)
The present article attempts to understand the central features of the foreign strategy of Mauricio Macri´s conservative Argentinian government (2015-2019). A close scrutiny of the final drive to successfully conclude negotiations between Mercosur and the European Union during the closing stages of Mr.Macri´s administration is performed. A qualitative method has been used, based on a detailed inspection of official sources, press reports and news stories covering the talks. It is possible to conclude that besides the Argentinian decision to go ahead with the talks and bring them to a positive conclusion, it was also necessary for the “Progressive” cycle in regional politics, to come to an end. This was greatly expedited by the impeachment of former Brazilian President Dilma Roussef, a development that allowed all Mercosur countries to be in the same page regarding the organization´s relationship with the European partners. The final outcome of the talks made it clear that the Argentinean government had finally accepted to remove all the obstacles that had obstructed its trade with Europe during the post-war period. Instead, a new approach was adopted, based on the belief that free trade would promote enhanced economic growth. The actions undertaken by the Macri administration leading into the opening of the dialogs resulting in the 2019 Agreement, underscore the limitations of his government in grasping the workings of the international system. Finally, this allows to reach a better understanding the main features of the Argentinean model of insertion in the world economy.